2021
DOI: 10.1038/s41585-021-00481-1
|View full text |Cite
|
Sign up to set email alerts
|

100 years of Bacillus Calmette–Guérin immunotherapy: from cattle to COVID-19

Abstract: Bacillus Calmette–Guérin (BCG) is the most widely used vaccine worldwide and has been used to prevent tuberculosis for a century. BCG also stimulates an anti-tumour immune response, which urologists have harnessed for the treatment of non-muscle-invasive bladder cancer. A growing body of evidence indicates that BCG offers protection against various non-mycobacterial and viral infections. The non-specific effects of BCG occur via the induction of trained immunity and form the basis for the hypothesis that BCG v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 153 publications
0
70
0
1
Order By: Relevance
“…This is consistent with recent data reported by Rivas and coworkers [71] and discussed in detail elsewhere [72] , indicating that history of BCG vaccination is associated with a decrease in the seroprevalence of anti-SARS-CoV-2 IgG and a lower number of subjects experiencing COVID-19-related clinical symptoms in a cohort of health-care workers. Notably, current studies are also based on the use of recombinant BCG activating the STING pathway to enhance the potency of the immune response [73] . While the interim results of the “ACTIVE” clinical trial aimed at evaluating the efficacy of BCG vaccination in protecting elderly patients against new infections seem to be encouraging [74] , more data are needed to eventually confirm whether BCG vaccination, alone or in combination, can indeed exert a protective effect against SARS-CoV-2 infection.…”
Section: Fostering Innate Antiviral Immunity For the Control Of Pandemic Viruses: Role Of Type I Ifnmentioning
confidence: 99%
“…This is consistent with recent data reported by Rivas and coworkers [71] and discussed in detail elsewhere [72] , indicating that history of BCG vaccination is associated with a decrease in the seroprevalence of anti-SARS-CoV-2 IgG and a lower number of subjects experiencing COVID-19-related clinical symptoms in a cohort of health-care workers. Notably, current studies are also based on the use of recombinant BCG activating the STING pathway to enhance the potency of the immune response [73] . While the interim results of the “ACTIVE” clinical trial aimed at evaluating the efficacy of BCG vaccination in protecting elderly patients against new infections seem to be encouraging [74] , more data are needed to eventually confirm whether BCG vaccination, alone or in combination, can indeed exert a protective effect against SARS-CoV-2 infection.…”
Section: Fostering Innate Antiviral Immunity For the Control Of Pandemic Viruses: Role Of Type I Ifnmentioning
confidence: 99%
“…Recently a multi-center retrospective cohort study including 12,185 bladder cancer patients with a follow-up of 3.5 to 7 years shows that the 2301 BCG-treated patients manifested more than 4-fold less risk for AD than those not treated with BCG [ 42 , 43 ]. On the other hand, the antituberculosis vaccine bacillus Calmette-Guérin (BCG) appears as preventative of the severity of coronavirus disease 2019 (COVID-19) [ 44 , 45 ]. From a life-course perspective, the role of infant vaccinations and boosters is fundamentally important in contributing to maintaining good health well into adulthood.…”
Section: At the Individual Level The Other Benefits Of Vaccines Are L...mentioning
confidence: 99%
“…Though BCG has been used for decades, the mechanisms of action and failure are not fully understood. Despite of high initial response rates, a study found that up to 42% of patients recurred after complete BCG-therapy, and 14% progressed 2,3 BCG is thought to act through activation of both the innate and adaptive immune systems, thereby promoting lasting antitumor effects 4 . Several immune cell types have proven necessary for BCG-response in vitro and in murine studies, including natural killer (NK) cells 5 , neutrophils 6 , and T-cells 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Though BCG has been used for decades, the mechanisms of action and failure are not fully understood. Despite of high initial response rates, a study found that up to 42% of patients recurred after complete BCG-therapy, and 14% progressed 2,3…”
Section: Introductionmentioning
confidence: 99%